Public participation in the preparation processes of political decisions in the Kyrgyz Republic (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The article discusses various approaches to the study of the process of political decision-making in the form of normative legal acts and the participation of Kyrgyz society at the stage of adoption of a legal act through the Unified Portal of Public Discussion of normative legal acts of the Kyrgyz Republic. It is noted that Kyrgyz citizens can independently initiate political decision-making in the form of normative legal acts and take part in the processes of their adoption, implementation and determination of results. Citizens can participate in the processes of their preparation only if a legal act is submitted to the Jogorku Kenesh in the form of a popular initiative. The possibility of using new forms of political participation of society in political decision-making processes in the form of normative legal acts is being considered.
Keywords: political decision, public administration, regulatory legal acts, public discussion, management decision, single portal, legislative initiative, Jogorku Kenesh (Parliament), initiative group, people’s initiative, crowdsourcing, political crowdsourcing